PSYCHOLOGICAL METHODS FOR INCREASING EMPLOYEE ENGAGEMENT AND SUSTAINABLE HIGH PRODUCTIVITY (American Journal of Pedagogical and Educational Research, 2025)
This article summarizes modern psychological approaches to increasing employee engagement and maintaining long-term high productivity. Key theoretical models (conditions of engagement, the Job model) are considered. Demands - Resources theory, self-determination theory), practical methods (job design, job crafting, psychological safety, goal-setting, feedback, and recovery), as well as principles for implementing and evaluating the effectiveness of interventions. Conclusions are drawn that a combination of organizational (resources, design) and individual-psychological (autonomy, meaning, and recovery) measures ensures the greatest sustainability of results.